(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
This study aims to determine the impact of service quality (tangibles, reliability responsiveness, assurance, and empathy) on customer’s loyalty in five stars hotels. To achieve the objectives of the study, a questionnaire was developed and distributed. The study population consists of all hotels customers in Malaysia and Jordan, and convenience sample was selected in this study pilot test 57 questionnaires. The study finds that there is a strong impact of service quality (tangibles, reliability responsiveness, assurance, and empathy) on customer’s loyalty in five stars hotels in Malaysia and Jordan. Based on the above mentioned results, a set of necessary recommendations was formulated, which enable the hotels to strengthen the relationship between perceived service quality and customers loyalty. Providing services with confidence and accuracy, employees training, and strengthen the culture of service quality are key factors.